DIAGNOSIS AND MANAGEMENT OF GASTROINTESTINAL BLEEDING FROM ANGIODYSPLASTIC LESIONS - V. A. Kashschenko; Ya. A. Nakatis; A. V. Lodygin; Е. G. Solonitsyn; D. V. Paspereza; E. L. Vasyukova; E. G. Beskrovniy (Вестник хирургии имени И.И. Грекова, 2018)
.